Effect of compost and compost-derived biochar on the growth of lettuce irrigated with water and treated wastewater - Panagiotis Regkouzas; Nancy Katie; Konstantinos Bontiotis; Alexandros Stefanakis (Nature-Based Solutions)
As climate change keeps progressing, the use of biochar and compost as nature-based materials emerges as sustainable alternative that can have a positive impact on agriculture. Such valuable organic materials produced from previously considered waste products are increasingly viewed as attractive nature-positive solutions to improve soil quality and fertility that could help in climate change mitigation and address sustainable development goals. In this study, compost and compost-derived biochar were produced from the organic fraction of municipal solid waste and tested as soil amendments for the cultivation of lettuce (Lactuca sativa L), irrigated with both tap water and secondary wastewater effluent. Physicochemical characterization of compost, biochar and soil showed that the investigated materials were not so rich, compared to biochars from different feedstocks but when applied to the soil for lettuce cultivation, they may provide a positive effect. The combined effect of the use of bio-based materials and irrigation with treated wastewater was found to lead to higher soil and crops quality. Longer crop growth cycles are necessary to clearly demonstrate the positive effect of biochar on crop yield. Such materials can effectively be used for sustainable agriculture, contributing to the promotion of nature-based solutions as useful tools that promote circular practices.